Determinants of capybara presence in afforestations of the lower delta of the Paraná river, Argentina - Fracassi, Natalia G. (2015)
The delta of the Paraná River in Argentina represents the southernmost stronghold for capybaras (Hydrochoerus hydrochaeris), but this area is highly modified due to commercial afforestations with Salicaceae. Water management (e.g. drainage of marshes) and land protections (e.g. polders) are carried out to improve field conditions for developing afforestations. To assess determinants of capybara presence within polder afforestations, its presence was surveyed in 2011?2013 along with 35 habitat and human-related variables at two spatial scales, in 53 watercourse-side sites. Using logistic regression, a habitat model was developed. Capybaras were present in 52.8% of sites. Water depth at the center of the watercourse had the strongest positive effect on capybara presence, followed by cover of reed marshes and cover of grass bush on the banks. Cover of adult poplar plantations showed a significant negative effect on capybara presence. Watercourses within polder afforestations can provide habitat for capybaras, although their use by these rodents depends on factors interacting at different scales.